Effects of lorcaserin (Belviq®) on nicotine- and food-maintained responding in non-human primates. (1st December 2017) - Jacobs, David S.; Barkin, Claire E.; Kohut, Michelle R.; Bergman, Jack; Kohut, Stephen J.
Highlights: Treatment with lorcaserin decreased nicotine self-administration. Lorcaserin had a modest decrease or no effect on responding for food reinforcement. Home-cage activity was decreased after acute treatment with lorcaserin. Further characterization of lorcaserin's utility for smoking cessation is warranted. Abstract: Background: Accumulating evidence suggests that the FDA-approved serotonin 5- HT2C receptor agonist, lorcaserin (Belviq®), may be a promising candidate for the management of substance use disorders, including nicotine addiction. The present study was conducted to determine the efficacy and selectivity of acute or continuous lorcaserin treatment for decreasing the reinforcing effects of nicotine in a primate species. Methods: Adult rhesus monkeys ( n = 4) with a history of nicotine self-administration (>2 years) responded for injections of nicotine (0.32–100 μg/kg IV) or food pellets under a fixed-ratio schedule of reinforcement during daily 100-min sessions. When responding was stable, lorcaserin was administered either as an acute pretreatment (0.1–1.0 mg/kg, IM) or by continuous infusion (0.1 mg/kg/hr, SC for 3–5 days). Daily activity patterns were also monitored immediately following experimental sessions. Results: Results indicate that acute lorcaserin pretreatment produced significant and dose-dependent decreases in nicotine-maintained responding across a >100-fold range of self-administered nicotine doses. Continuous lorcaserin treatment decreased intake of 10 μg/kg/inj nicotine to about 50% of baseline values. Food-maintained responding was only moderately decreased in 3 of 4 subjects after acute administration and unaffected in all subjects during continuous treatment. Daily activity also was significantly decreased—to ≤50% of control values—following experimental sessions in which acute lorcaserin was administered. Conclusions: These data indicate that lorcaserin reduces IV self-administration of nicotine at a dose that decreases motoric activity but less consistently disrupts food-maintained responding. Further research into lorcaserin's potential utility for the management of nicotine dependence is warranted.